Non-linear dynamics of a tower orchard sprayer based on an inverted pendulum model - Sartori Junior, Sergio; Balthazar, José Manoel [UNESP]; Pontes Junior, Bento Rodrigues [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
A modern form of air-assisted orchard sprayer consists of a vertical structure, or tower fitted with spray nozzles assisted by fans. The sprayer travels between crop rows and the tower is either mounted on an agricultural tractor on a trailer, with or without suspension. In some situations, lateral movement of vertical structure can negatively affect the results of the treatment. Thus, it is important to recognize and possibly control these lateral movements. In this paper a non-linear dynamic model, based on an inverted pendulum model, is developed to analyse the rolling movement of a moving orchard tower sprayer. The governing equations of movement were deduced using Lagrange's equations and Hamilton's principle and were implemented using the MatLab (R) - Simulink (R). Using numerical simulations, a dynamic analysis of the roll movements of the sprayer under different configurations and sinusoidal excitations was presented. (C) 2008 IAgrE. Published by Elsevier Ltd. All rights reserved.